Preliminary results of intraspecific sterlet hybrid (Siberian sterlet × sterlet) rearing under intensive conditions - Feledi, Tibor; Lengyel, Svetlana; Rónyai, András (Acta Agraria Debreceniensis, 2012)
Due to early maturation and a small size, sterlet (Acipenserrut-henus) is a very advantageous fish for intensive sturgeon farming with regard to caviar production. According to our previous observations, the growth potential of Siberian sterlet (A.ruthenusmarsiglii) is higher than that of the European one. In our experiment, sterlet and an intraspecific hybrid (Siberian sterlet × sterlet) were tested under intensive tank conditions. During the 8 weeks of the experiment, survival, growth and size heterogeneity were investigated. According to the results, there were no significant differences in survival and growth but the size heterogeneity was higher in the hybrid. It is supposed that, in our trial, the applied water  temperature range (24.0–25.5 °C) was optimal for sterlet, but was probably above the optimal range for the hybrid.